2012
DOI: 10.1007/s10339-012-0460-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting spatial descriptions in visual scene analysis

Abstract: The reliable automatic visual recognition of indoor scenes with complex object constellations using only sensor data is a nontrivial problem. In order to improve the construction of an accurate semantic 3D model of an indoor scene, we exploit human-produced verbal descriptions of the relative location of pairs of objects. This requires the ability to deal with different spatial reference frames (RF) that humans use interchangeably. In German, both the intrinsic and relative RF are used frequently, which often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This disagreement and the potential for ambiguities has led to an extensive body of psycholinguistic investigations of which factors contribute to the selection and processing of spatial FOR, mostly using monolog studies. The factors identified range from functional relations between objects (Carlson-Radvansky and Radvansky, 1996) to motion characteristics (Levelt, 1984), gravity (Friederici and Levelt, 1990), priming effects (Watson et al, 2004; Carlson and Van Deman, 2008; Johannsen and de Ruiter, 2013), scene type (Johannsen and de Ruiter, 2013), and properties of the object configuration such as the rotation of the reference object and the position of the located object (Ziegler et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disagreement and the potential for ambiguities has led to an extensive body of psycholinguistic investigations of which factors contribute to the selection and processing of spatial FOR, mostly using monolog studies. The factors identified range from functional relations between objects (Carlson-Radvansky and Radvansky, 1996) to motion characteristics (Levelt, 1984), gravity (Friederici and Levelt, 1990), priming effects (Watson et al, 2004; Carlson and Van Deman, 2008; Johannsen and de Ruiter, 2013), scene type (Johannsen and de Ruiter, 2013), and properties of the object configuration such as the rotation of the reference object and the position of the located object (Ziegler et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…However, following the attempts to specify FOR preferences (as described above), it has been shown that there is a general preference for the intrinsic FOR in specific object configurations (Ziegler et al, 2012). This study also demonstrated an effect of the located object’s position with regard to the reference object’s FOR.…”
Section: Introductionmentioning
confidence: 99%